2011
DOI: 10.5194/angeo-29-263-2011
|View full text |Cite
|
Sign up to set email alerts
|

Non-stationarity of the quasi-perpendicular bow shock: comparison between Cluster observations and simulations

Abstract: Abstract. We have performed full particle electromagnetic simulations of a quasi-perpendicular shock. The shock parameters have been chosen to be appropriate for the quasiperpendicular Earth's bow shock observed by Cluster on 24 January 2001 (Lobzin et al., 2007). We have performed two simulations with different ion to electron mass ratio: run 1 with m i /m e = 1840 and run 2 with m i /m e = 100. In run 1 the growth rate of the modified two-stream instability (MTSI) is large enough to get excited during the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 21 publications
7
31
0
1
Order By: Relevance
“…Multiple magnetic fluctuations in and around collisionless shock waves have been shown to be consistent with magnetosonic-whistler waves, and these fluctuations are predicted to have multiple sources including but not limited to dispersive radiation [e.g., Tidman and Northrop, 1968;Kennel et al, 1985;Krasnoselskikh et al, 2002], diffuse ions [e.g., Scholer et al, 2003;Tsubouchi and Lembège, 2004], reflected gyrating ion beams [e.g., Wu et al, 1983;Riquelme and Spitkovsky, 2011;Comişel et al, 2011], field-aligned ion beams [e.g., Akimoto et al, 1993], and streaming and anisotropic electron velocity distributions [e.g., Sentman et al, 1983]. Theory [e.g., Wu et al, 1983;Cairns and McMillan, 2005] predicts that they can stochastically accelerate electrons parallel to B o and heat ions perpendicular to B o when propagating at highly oblique angles, which has been supported by observations [e.g., Wilson et al, 2012].…”
Section: Low-frequency Wavesmentioning
confidence: 99%
“…Multiple magnetic fluctuations in and around collisionless shock waves have been shown to be consistent with magnetosonic-whistler waves, and these fluctuations are predicted to have multiple sources including but not limited to dispersive radiation [e.g., Tidman and Northrop, 1968;Kennel et al, 1985;Krasnoselskikh et al, 2002], diffuse ions [e.g., Scholer et al, 2003;Tsubouchi and Lembège, 2004], reflected gyrating ion beams [e.g., Wu et al, 1983;Riquelme and Spitkovsky, 2011;Comişel et al, 2011], field-aligned ion beams [e.g., Akimoto et al, 1993], and streaming and anisotropic electron velocity distributions [e.g., Sentman et al, 1983]. Theory [e.g., Wu et al, 1983;Cairns and McMillan, 2005] predicts that they can stochastically accelerate electrons parallel to B o and heat ions perpendicular to B o when propagating at highly oblique angles, which has been supported by observations [e.g., Wilson et al, 2012].…”
Section: Low-frequency Wavesmentioning
confidence: 99%
“…However, it has been argued by Krasnoselskikh et al (2013) that the artificial values of the electron plasma-to-electron cyclotron frequency ratio, necessitated by the simulations (e.g. Comişel et al 2011), produce electric fields in the simulations at least two orders of magnitude larger than those observed in heliospheric shocks. This underlines the importance of interpreting simulation results and the importance of validation against observations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Comişel et al (2011) performed 1-D PIC simulations and made comparisons with the same shock crossing studied by Lobzin et al (2007). Based on the simulation results, they concluded that the high-frequency fluctuations were due to the modified two-stream instability (MTSI), rather than the whistler gradient catastrophe model of Krasnoselskikh et al (2002).…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly due to most studies of shock crossings being near the Earth where the Mach numbers typically range from low to modest (M A = 2-8). While some observations have been reported at Earth's bow shock [Lobzin et al, 2007], they remain open to interpretation [Comisel et al, 2011].…”
Section: Introductionmentioning
confidence: 99%